2023
DOI: 10.3390/microorganisms11010209
|View full text |Cite
|
Sign up to set email alerts
|

A Search for Tick-Associated, Bronnoya-like Virus Spillover into Sheep

Abstract: Tick-borne diseases are responsible for many vector-borne diseases within Europe. Recently, novel viruses belonging to a new viral family of the order Bunyavirales were discovered in numerous tick species. In this study, we used metatranscriptomics to detect the virome, including novel viruses, associated with Ixodes ricinus collected from Romania and France. A bunyavirus-like virus related to the Bronnoya virus was identified for the first time in these regions. It presents a high level of amino-acid conserva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The nymphs were grouped into pools of 15 specimens (116 pools) and adults were treated individually. Furthermore, 202 adult ticks (20 pools) were directly collected from sheep in Eastern Romania, Danube Delta region, during October 2020 and May 2021, as described previously [22]. Additionally, 315 adult ticks (39 pools) were collected using the flagging method between March and September 2015, in Iasi County, Romania.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The nymphs were grouped into pools of 15 specimens (116 pools) and adults were treated individually. Furthermore, 202 adult ticks (20 pools) were directly collected from sheep in Eastern Romania, Danube Delta region, during October 2020 and May 2021, as described previously [22]. Additionally, 315 adult ticks (39 pools) were collected using the flagging method between March and September 2015, in Iasi County, Romania.…”
Section: Methodsmentioning
confidence: 99%
“…Among the core virome, apart from sequences belonging to the Phenuiviridae or Nairoviridae families (see below), sequences related to the Peribunyaviridae family mapped onto six novel strains of Bronnoya-like virus (BroBV-like) which were present in all tick pools [22]. BroBV virus was detected in Norway [19], Croatia [24], and Romania [22] and has been described so far only in I. ricinus ticks. The Flaviviridae family was detected in all libraries but was the most abundant in ticks from Alsace region due to the presence of numerous Jingmen tick virus (JMTV)-related reads.…”
Section: Diversity and Composition Of The Virome Of Ixodes Ricinus In...mentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, in the study of the tick virome, modern research approaches (metagenomic and metatranscriptomic) have been used that have revealed an enormous number of putative new pathogens [ 1 ]. Such information greatly enriches knowledge of the natural diversity of possible pathogens in different tick species [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tick-borne viruses are a diverse group that includes members of Flaviviridae, Bunyavirales, Orthomyxoviridae and Reoviridae (Johnson et al 2023). Probably this is why the viral component of the tick microbiome has recently been studied quite extensively through meta-RNA sequencing (e.g., Bratuleanu et al 2023;Cai et al 2023;Guo et al 2022;Harvey et al 2019;Kong et al 2022;Ni et al 2023;Pettersson et al 2017;Tokarz et al 2018;Xu et al 2021;Z. Yang et al 2023).…”
Section: Ticks (Arachnida: Ixodida)mentioning
confidence: 99%